Atatürk Kitaplığı'nda Bulunan Bosna-Hersekle İlgili Yazmalar - Nail Bayraktar (Türk Kütüphaneciliği)
Turkish libraries hold a large number of books written by Bosnian authors. In this article some manuscripts from the Atatürk Municipal Library have been introduced. Manuscripts written by Bosnian authors are being microfilmed currently. The author suggests that manuscripts held by Macedonian and Kosova libraries should also be microfilmed.